PENGARUH LATIHAN IMAGERY TERHADAP HASIL PUKULAN GATE IN JARAK 30 M PADA UKM WOODBALL UNIVERSITAS PGRI SILAMPARI - Wawan Syafutra; M Eric Kantona (Jurnal Tunas Pendidikan, 2023)
ABSTRACT The purpose of this study was to find out how the effect of imagery training on the results of hitting the gate in a distance of 30m in the UNPARI woodball student activity unit. The type of research this time was experimental research in the form of a one-group pretest-posttest design. In this study, a sample of 10 people who were members of the UNPARI woodball UKM were then given an imagery training program. The instrument used was the 30M distance woodball skill test. The data analysis technique used SPSS 22 with the Wilcoxon singned rank test. The results of the Z data analysis obtained are -3,000 with a p value of Asymp. Sig. (2-tailed) of .003 is smaller <.005, so this result is that there is an influence on the differences in pretest and posttest data. These results also show that hypothesis a: is accepted and Hypothesis o: is rejected because it complies with the decision rules of hypothesis testing. If Ha is accepted then Ho is rejected Ha's statement reads "The effect of Imagery training can increase the results of Gate-in shots for beginner athletes at UKM Woodball, PGRI Silampari University. Keywords: Woodball, imagery training, hitting, gate in